2009
DOI: 10.1111/j.1365-2109.2008.02114.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature, stocking density and fish size on the ammonia excretion in palmetto bass (Morone saxatilis×M. chrysops)

Abstract: Three temperature levels (18, 23 and 28 1C), three stocking density levels (0.72, 1.42 and 2.84 kg m À 3 ) and two sizes of groups (averaging 104 and 173 g respectively) were used to conduct experiments on the e¡ect of temperature, stocking density and ¢sh size on the ammonia excretion (AE) of palmetto bass (Morone saxatilis  M. chrysops). The AE increased with the increase in temperatures by a signi¢cant degree (Po0.05) among di¡erent temperature groups. There appeared to be a tendency towards increase of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
(50 reference statements)
1
9
0
1
Order By: Relevance
“…The pattern of postprandial ammonia excretion in the present experiment was consistent with previous reports for HSB (Rawles et al, 2009) and European sea bass (Ballestrazzi et al, 1998;Dosdat et al, 1996;Robiana et al, 1999). In fact, ammonia excretion by fish peaks from 2-10 h following a meal and is affected by fish size and water temperature (Cheng et al, 2005;Dosdat et al, 1996;Forsberg, 1997;Leung et al, 1999;Liu et al, 2009;Luo and Xie, 2009). The amounts of N intake excreted as ammonia following a meal in the present experiment were consistent with the ranges reported for a variety of fish tested under a range of experimental conditions (Beamish and Thomas, 1984;Cheng et al, 2005;Dosdat et al, 1996;Forsberg, 1997;Kaushik, 1980;Luo and Xie, 2009;Rawles et al, 2009;Robiana et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…The pattern of postprandial ammonia excretion in the present experiment was consistent with previous reports for HSB (Rawles et al, 2009) and European sea bass (Ballestrazzi et al, 1998;Dosdat et al, 1996;Robiana et al, 1999). In fact, ammonia excretion by fish peaks from 2-10 h following a meal and is affected by fish size and water temperature (Cheng et al, 2005;Dosdat et al, 1996;Forsberg, 1997;Leung et al, 1999;Liu et al, 2009;Luo and Xie, 2009). The amounts of N intake excreted as ammonia following a meal in the present experiment were consistent with the ranges reported for a variety of fish tested under a range of experimental conditions (Beamish and Thomas, 1984;Cheng et al, 2005;Dosdat et al, 1996;Forsberg, 1997;Kaushik, 1980;Luo and Xie, 2009;Rawles et al, 2009;Robiana et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, temperature has dramatic effect on the metabolic rate in fish, and is also related to the ammonia‐N excretion rates. Related researchers also found a significant increase in ammonia‐N excretion with temperature in Lake Inari Arctic charr ( Salvelinus alpinus ) and Hybrid‐striped bass ( Morone saxatilis × M. chrysops ) (Lyytikäinen & Jobling ; Liu, Yang & Chen ). The results of the present study clearly indicated that, as the temperature increased, the ammonia‐N excretion rates for fasted fish of both species also significantly increased ( P < 0.05).…”
Section: Discussionmentioning
confidence: 87%
“…Liu et al . () found a sharp peak in Hybrid‐striped bass ( Morone saxatilis × M . chrysops ) fed once or twice a day was at 4 h after feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The increased amount of feed supplied in the last months of the study confirmed this information and corroborated the hereinrecorded results. Villarreal and Torres (2011) and Fu-Guang et al (2009) reported that 60% to 80% of the total nitrogen excreted corresponds to ammonium.…”
Section: Resultsmentioning
confidence: 99%